Vermicomposting of coir pith and cow manure: Influence of initial total phenolic content on earthworms’ performance - Kanokwan Pundee; Saengchai Akeprathumchai; Sudarut Tripetchkul (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose: Vermicomposting of phenolics-rich lignocellulosic materials takes a long time to reach maturity, while worm mortality and weight loss are often encountered. Phenolic compounds have antimicrobial properties which may affect the vermicomposting process. The present study aims at investigating the effect of the initial total phenolic content (TPC) on coir pith vermicomposting. Method: The earthworm activities and performance during vermicomposting of coir pith and cow manure containing 4.8 (T0), 6.4 (T1), 7.2 (T2), 8.8 (T3), 10.3 (T4) and 12.7 (T5) mg initial TPC g-1 substrate using Eudrilus eugeniae were investigated. Results: Total carbon loss increased as initial TPC increased and only T0 and T1 reached maturity. Earthworm mortality and weight loss increased as initial TPC of materials increased in a concentration dependent manner. High performance liquid chromatography (HPLC) results showed that the total numbers of water-soluble phenolics of coir pith and cow manure were, respectively, 17 and 16 out of which 5 and 4 were unique to coir pith and cow manure, respectively. By the end of vermicomposting, almost all of phenolics present in cow manure disappeared while those in coir pith remained intact, albeit, reduced in concentrations. 4-hydroxybenzoic acid and p-coumaric acid were detected in all treatments. Disappearance of 4.90 and 6.35 minute-peaks was observed with T0, T1 and T2 whilst a new phenolic (5.30 minute-peak) was detected only in T1 indicating the better degradation of phenolic compounds. Conclusion: Results indicated a significant role of initial TPC on earthworm activities during coir pith vermicomposting. Highlight